HOW ISLAMIC SOCIAL FUNDS SUPPORT SUSTAINABLE DEVELOPMENT GOALS DURING COVID OUTBREAK? THE ROLE OF RELIGIOSITY, TRUST, AND PERCEIVED BEHAVIORAL CONTROL - Yunice Karina Tumewang; Intan Tri Annisa; Faaza Fakhrunnas (Share: Jurnal Ekonomi dan Keuangan Islam, 2021)
Islamic social fund is proliferating in this most populous Muslim country, particularly in the time of this pandemic. During early 2020, there was a substantial growth of the collection of Islamic social funds for nearly 70% compared to the last year's figure, which is mainly driven by the digitalization of social fund payment. This paper aims to elaborate on the determinants of Islamic social funds to support Sustainable Development Goals (SDGs) program by looking at the intention of the society to donate through the e-payment platform. This study involves 212 users of digital social payments by distributing an online questionnaire. Data analysis was performed using a Structural Equation Model technique in AMOS. This study reveals that religiosity, trust, and perceived behavioral control have a positive and significant effect on the intention to donate through online platforms. Furthermore, when it comes to a specific categorized SDG program, the people sector is the highest priority, followed by Prosperity and Peace sectors.========================================================================================================ABSTRAK – Bagaimana Dana Sosial Islam mendukung Sustainable Development Goals dalam Masa Covid-19? Analisis Peran Religiositas, Kepercayaan, dan Persepsi Kontrol Perilaku. Dana sosial Islam berkembang pesat di negara berpenduduk Muslim terbesar ini terutama di saat pandemi. Selama awal tahun 2020, terjadi pertumbuhan tajam atas dana sosial Islam yang berhasil dikumpulkan yaitu sebanyak 70% dibandingkan dengan tahun lalu. Hal ini utamanya didorong oleh digitalisasi pembayaran dana sosial. Penelitian ini bertujuan untuk mengelaborasi determinan pembayaran dana sosial Islam dalam mendukung program SDGs dengan melihat niat masyarakat untuk berdonasi melalui platform pembayaran elektronik. Penelitian ini melibatkan 212 pengguna pembayaran sosial digital dengan menyebarkan kuesioner online. Analisis data dilakukan dengan teknik Structural Equation Model (SEM) di AMOS. Hasil penelitian ini menunjukkan bahwa religiusitas, kepercayaan, dan persepsi tentang control perilaku berpengaruh signifikan positif terhadap niat berdonasi melalui platform online. Terlebih, jika kita teliti terkait program SDG, sektor yang erat berkaitan langsung dengan ‘People’ menempati posisi teratas, diikuti oleh sektor ‘Prosperity’ dan ‘Peace’.